49.5k views
3 votes
Find the solution to the system of equations.

y= 2x + 3

y= -3x + 3

User CFrei
by
5.7k points

1 Answer

5 votes

Answer:

(0, 3 )

Explanation:

Given the 2 equations

y = 2x + 3 → (1)

y = - 3x + 3 → (2)

Since both equations express y in terms of x we can equate them, that is

2x + 3 = - 3x + 3 ( add 3x to both sides )

5x + 3 = 3 ( subtract 3 from both sides )

5x = 0 ⇒ x = 0

Substitute x = 0 into (1)

y = 0 + 3 = 3

Solution is (0, 3 )

User Edgar Ortega
by
5.7k points